PRESENT SITUATION AND FUTURE PERSPECTIVE OF BUFFALO PRODUCTION IN ASIA - T. N. Pasha; Z. Hayat (Journal of Animal and Plant Sciences, 2012)
Buffalo, a triple purpose animal, provides milk, meat and mechanical power to mankind. Due to its highly nutritious milk, leaner meat and best draught power for wet environments buffalo offers immense potential for the improvement of livelihood. It is a versatile animal found across the world from tropical to temperate regions and even at the altitudes of more than 7000 feet. Buffalo can efficiently convert low quality feed stuffs like straws and agro-industrial waste into human food, improve soil structure through bio fertilizer and a financial asset which can be sold when needs arise. Although, buffalo is the flagship of all agricultural revolutions; green, white and red but unfortunately has been neglected in the past. Therefore, aim of this paper is to evaluate present situation and future perspectives of buffalo production in Asia.
Keywords: Buffalo; Asia; present situation; future prospective